Top Management Team Composition and Firm Performance - Lizares, Regina M. (Philippine Management Review; Vol 25 (2018), 2019)
This study investigated the relationship between top management team’s (TMT) demographic characteristics and firm performance of listed Philippine holding firms.  The TMTs helming these companies have had significant economic impact given their firms large—often dominant—presence in diverse industries.  Using organizational demography, a panel of TMT’s demographic characteristics (tenure, educational and functional background, age, and gender) and firm performance (revenue growth and return on assets) were regressed.  Results showed that increased compositional difference in team member’s functional background and gender negatively affected firm performance.  Hence, TMT composition matters and the thoughtful selection of its members vital.